Kehidupan Agama dan Kebudayaan Islam (Tinjauan Empiris Clifford Geertz) - Zubair, Abi Amar (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study discusses the study of the Slametan Tradition as part of Islamic culture in Geertz's study in Mojokuto in 1953-1954. The slametan tradition is carried out by the abangan community with the initial and basic assumption that emerged in society that they were a group of idol worshipers, full of superstition, and low class. Currently, the Slametan Tradition is inherent in the Islamic-NU community as Islam that is open to local wisdom. This research aims to 1) Find out Clifford Geertz's views on religion. 2) Analyze the Value of Local Wisdom in the Slametan Tradition. 3) Identify the characteristics of Santri and Priyayi from Geertz's research. The type of research uses a descriptive qualitative approach with a literature study method—data collection methods with primary and secondary sources. Data analysis includes data collection, reduction, presentation, and concluding. The study results show that religion, according to Geertz, is a symbol that establishes strong motivation and mood, is absorbed, and lasts a long time in individuals by formulating and wrapping concepts about general order, such as factual radiation, to motivation and mood. Islam by Geertz is grouped into Abangan, Santri, and Priyayi groups. The local wisdom value of the Slametan Ceremony is the historical, religious, cooperation, and moral discipline aspects. In conclusion, the Slametan Tradition has noble values as a manifestation of increasing religious spirituality and relating to fellow human beings.